The laws of belief ranking theory and its philosophical applications - Spohn, Wolfgang (Oxford : Oxford University Press, 2012)
Wolfgang Spohn presents a full account of the dynamic laws of belief, by means of ranking theory, a relative of probability theory which he has pioneered since the 1980s. He offers novel insights into the nature of laws, the theory of causation inductive reasoning and its experiential base, and a priori principles of reason.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Reason; Causation; Idea (Philosophy)